An Analysis of English Vocabulary Learning Experience Through Self-Regulated Learning (SRL) Strategies Among English Education Students at a University in Kebumen - Andriyani, Fitri; Asroriyah, Atik Muhimatun (Universitas Islam Negeri Raden Intan Lampung, 2025)
Vocabulary mastery is a fundamental aspect of English language learning, but many college students experience difficulties in remembering and applying vocabulary effectively. Self-Regulated Learning (SRL) strategies, which encourage independent and reflective learning, offer potential benefits in vocabulary development, but further study is needed in practical contexts. This study aims to analyze students' experiences in learning English vocabulary using SRL strategies and to identify internal and external factors that influence their learning behavior. A qualitative approach with a phenomenological design was used in accordance with the Standards for Reporting Qualitative Research (SRQR) guidelines. Fifteen final-year students from the English language education program at a university in Kebumen were purposively selected based on the results of a 20-item Likert-scale SRL questionnaire. Data were collected through questionnaires, semi-structured interviews, and documentation. Thematic analysis was conducted based on the six stages proposed by Braun and Clarke and the SRL framework by Zimmerman, which includes the planning, implementation, and self-reflection phases, as well as metacognitive, motivational, and behavioral components. The research findings indicate that students actively apply SRL strategies in vocabulary learning, including goal setting, use of digital media (such as Quizlet, YouTube), reflective journal writing, and adjustment of methods based on evaluation. Students demonstrated high motivation and perseverance, although time management and planning strategies still varied. Questionnaire results reinforced qualitative findings and confirmed student engagement in SRL principles. Overall, SRL strategies play a significant role in supporting independent, strategic, and reflective vocabulary learning in higher education settings.